Endoplasmic reticulum stress promotes breast cancer cells to release exosomes circ_0001142 and induces M2 polarization of macrophages to regulate tumor progression - Chong Lu; Wei Shi; Wenjing Hu; Yu Zhao; Xiangwang Zhao; Fang Dong; Yue Xin; Tao Peng; Chunping Liu (Pharmacological Research, 2022)
Breast cancer (BC) has a high morbidity and mortality rate. It is imperative to explore the pathogenesis of BC in order to find potential prognostic biomarkers and therapeutic targets. This study screened and verified the differential expression of circ_0001142 in BC tissues and cell lines through bioinformatics and qRT-PCR. Perform dual luciferase reporter gene assay and pull-down detection to verify the correlation between circ_0001142 and miRNA-361–3p and between miR-361–3p and PIK3CB. QRT-PCR, flow cytometry and ELISA were used to study the regulatory effects and regulatory mechanisms of different treatment groups on macrophage polarization. The role of exosomes circ_0001142 in the tumor microenvironment and its influence on BC growth, metastasis and macrophage polarization were investigated through in vivo and in vitro studies. We first found that circ_0001142 is highly expressed in BC. In addition, ERs promote the secretion of tumor exosomes, enhance the entry of circ_0001142 into macrophages and interfere with the process of autophagy and polarization. Finally, it was found that the circ_0001142/miR-361–3p/PIK3CB pathway plays an important role in the polarization of macrophages.